The effect of endometrial thickness and pattern measured by ultrasonography on pregnancy outcomes during IVF-ET cycles - Zhao Jing; Zhang Qiong; Li Yanping (BMC, 2012)
Abstract Background To study the effect of endometrial thickness and pattern measured using ultrasound upon pregnancy outcomes in patients undergoing IVF-ET. Method One thousand nine hundred thirty-three women undergoing IVF treatment participated in the study. We assessed and recorded endometrial patterns and thickness on the day of human chorionic gonadotropin (hCG) administration. Receiver operator curves (ROC) were used to determine the predictive accuracy of endometrial thickness. Cycles were divided into 3 groups depending on the thickness (group 1: ≤ 7 mm; group 2: > 7 mm to ≤ 14 mm; group 3: > 14 mm). Each group was subdivided into three groups according to the endometrial pattern as follows: pattern A (a triple-line pattern consisting of a central hyperechoic line surround by two hypoechoic layers); pattern B (an intermediate isoechogenic pattern with the same reflectivity as the surrounding myometrium and a poorly defined central echogenic line); and pattern C (homogenous, hyperechogenic endometrium). Clinical outcomes such as implantation and clinical pregnancy rates were analyzed. Results The endometrial thickness predicts pregnancy outcome with high sensitivity and specificity. The cutoff value was 9 mm. The implantation rate and clinical pregnancy rate in group 3 were 39.1% and 63.5%, respectively, which were significantly higher than those in group 2 (33.8% and 52.1%, respectively) and group 1 (13% and 25.5%, respectively). Among those with Pattern A, the implantation rate and clinical pregnancy rate were 35.3% and 55.2%, respectively, which were significantly higher than among women with Pattern B (32.1% and 50.9%, respectively) and Pattern C (23.4% and 37.4%, respectively). In groups 1 and 3, clinical pregnancy and implantation rates did not show any significant differences between different endometrial patterns (P > 0.05), whereas in group 2, the clinical pregnancy rate and implantation rate in women with pattern A were significantly higher than those with pattern B or C (P < 0.05). Conclusions Endometrial thickness and pattern independently affect pregnant outcomes. Combined endometrial thickness and pattern could not predict the outcome of IVF-ET when endometrial thickness was < 7 mm or >14 mm, while a triple-line pattern with a moderate endometrial thickness appeared to be associated with a good clinical outcome.